APLIKASI PENGAMANAN FILE GAMBAR MENGGUNAKAN ALGORITMA ELGAMAL - Pardede, Akim Manaor Hara (Journal Information System Development (ISD), 2018)
The growing use of information technology in helping human work in various types of activities involving computers as the media, then the issue of security and confidentiality is one very important aspect in the information system of a data, message, and information. Encryption is the best way to secure device and data information. In everyday codes are usually used to mean an encryption method or concealment of meaning. In cryptography, the elgamal algorithm can be used to encrypt and decrypt the image file. Elgamal algorithm can help maintain the security of image file so as to avoid the theft / damage to image file from irresponsible person.